Implementation of Environmental Awareness in the Legon Wetan Mangrove Area, Legon Kulon District, Subang Regency - Afriza, Lia; Larasati, Ajeng Ramadhita; Salsabila, Siti Reisa; Fitriyani, Yuni (Jurnal Toursci, 2025)
Background. The mangrove ecosystem in Legon plays a vital role in maintaining the balance of the coastal ecosystem while preserving economic potential through the development of ecotourism and products based on local resources. However, challenges in the form of environmental degradation and low community participation are the main obstacles in the utilization of this potential. Purpose. Increase awareness, capacity, and the active role of local communities in mangrove conservation through a community-based conservation (CBC) approach. The methods used include area mapping, environmental socialization and education, technical training on conservation and processing of mangrove-based products, coastal clean-up and replanting actions, and the formation of local driving communities. Result. The results of the activity included increased community participation, the formation of the "Legon Mangrove Friends Community" as a sustainable conservation partner, the preparation of technical training modules, and the development of several strategic recommendations. Conclusion. These recommendations include zoning-based management (rehabilitation, education/ecotourism, and core protection), periodic evaluations, the development of pilot products as regional icons, and the integration of green economic value chains to strengthen conservation behaviors. Analysis of 4A (Attraction, Accessibility, Amenities, and Ancillary Services) shows that the Legon mangrove area offers conservation-based ecotourism attractions, although there is still a need for improved accessibility, more facilities, and newly formed institutions. Implementation. These results affirm the importance of collaboration among the community, government, and academia in achieving sustainable mangrove management, while opening opportunities to improve the welfare of coastal communities. Keywords: mangroves, community-based conservation, ecotourism, green economy, community service